Application of Style Leadership Transformational in Islamic Education Institutions - Wahyudin, Aji; Furqon, Muhamad; Prabowo, Galuh; Zawawi, Ahmad Abdullah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze the application of transformational leadership style in Islamic educational institutions. In the context of Islamic educational institutions, the application of this leadership style is expected to improve the quality of education, build a positive work culture, and encourage the holistic development of the potential of students and staff. This research aims to explore the importance of the role of transformational leadership in Islamic educational institutions and its impact on various aspects of operations and learning. The research uses a qualitative approach with this type of literature study research using data collection techniques using several literature studies such as books, scientific journals, and supporting documentation. The results of this research show that transformational leadership is critical in facing contemporary challenges and ensuring that Islamic educational institutions do not only focus on academic achievement but also on developing student character through Islamic values. There are many phenomena that researchers have found in several Islamic educational institutions, for example: many teachers resign every year, they lack motivation and awareness of their duties as teachers or carry out their duties only because of rewards or punishments, and a lack of trust and loyalty towards school institutions. By implementing this transformational leadership style, it provides several positive impacts, the role of the principal is a model, encouraging subordinate performance, harmonizing the work environment, empowering employees, acting based on a value system, continuously improving their abilities, and having the ability to overcome complex situations. So with this research, it is hoped that the results of this research will be that this transformational leadership style can be applied to Islamic educational institutions, that have not yet used this leadership style, especially institutions that have a large number of students, both private and state because the results show that the transformational leadership style is very effectively applied to educational institutions today.